Efecto antimicrobiano de nanopartículas de plata en algunos ambientes - Calvo Olvera, Diana Alexandra; Rojas Avelizapa, Luz Irene; Rojas Avelizapa, Norma Gabriela (Universidad Pedagógica y Tecnológica de Colombia - UPTC, 2022)
The resistance of bacterial strains to antimicrobial agents and biofilm-associated infections causes considerable economiclosses and worldwide deaths. If this problem continues it is estimated that in 2050, about 10 million human deaths couldoccur per year and the costs would reach 1 trillion USD globally. Most of the studies evaluating the antimicrobial effect ofan antimicrobial agent focus on pure bacterial cultures, even when it is known that microorganisms live in communities interacting with each other, causing a less efficient antimicrobial effect on target compounds. Because of previous data, it is necessary the search for alternative and effective methods that, at the same time, do not generate bacterial resistance;silver nanoparticles (AgNPs) can be an excellent alternative; moreover, the evaluation of these antimicrobial agents onmicrobial communities from environmental samples are needed. In this paper, we synthesized spherical AgNPs by biological and chemical methods with an average diameter of 10.32 and 9.53 nm respectively; we evaluated the antimicrobial effect of both in microbial populations that came from three different environmental samples (computer keyboard, tap water, and pharyngeal exudate). Results showed that both AgNPs are excellent antimicrobial agents obtaining for both inhibition percentages higher than 90%.